2010
DOI: 10.1677/jme-10-0010
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and spatial dynamics of protein kinase A signaling organized by A-kinase-anchoring proteins

Abstract: Protein phosphorylation is the most common post-translational modification observed in cell signaling and is controlled by the balance between protein kinase and phosphatase activities. The cAMP-protein kinase A (PKA) pathway is one of the most studied and well-known signal pathways. To maintain a high level of specificity, the cAMP-PKA pathway is tightly regulated in space and time. A-kinase-anchoring proteins (AKAPs) target PKA to specific substrates and distinct subcellular compartments providing spatial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
145
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 107 publications
(64 reference statements)
2
145
0
2
Order By: Relevance
“…3 In 3T3-L1 adipocytes, knockdown of CD36 reduces hormone-sensitive lipase phosphorylation and triglyceride lipolysis in part via altering cellular cAMP (70). cAMP levels and signaling are regulated by phosphodiesterases and PKA-anchoring proteins with tissue-specific expression that provides compartmentalization of signals mediating the effects of various regulators (71). Further work is needed to explore how CD36 influences the cAMP/PKA pathway that may vary with cell type and interacting ligand.…”
Section: Discussionmentioning
confidence: 99%
“…3 In 3T3-L1 adipocytes, knockdown of CD36 reduces hormone-sensitive lipase phosphorylation and triglyceride lipolysis in part via altering cellular cAMP (70). cAMP levels and signaling are regulated by phosphodiesterases and PKA-anchoring proteins with tissue-specific expression that provides compartmentalization of signals mediating the effects of various regulators (71). Further work is needed to explore how CD36 influences the cAMP/PKA pathway that may vary with cell type and interacting ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Binding to AKAPs is essential for the spatial and temporal regulation of cAMP/PKA signaling ( Fig. 1) (Smith et al 2006, Pidoux & Tasken 2010). Mice with global or conditional mutants of R subunits, C subunits, or AKAPs have been generated (Kirschner et al 2009) and greatly enhanced our understanding of the role of cAMP/PKA in different physiological and pathological processes, such as neural synaptic plasticity (Rosenmund et al 1994), cardiac hypertrophy (Antos et al 2001, Enns et al 2010, tumor progression (Kirschner et al 2000), and glucose homeostasis (Niswender et al 2005, Willis et al 2011).…”
mentioning
confidence: 99%
“…To date 47 human AKAP genes have been identified that encode proteins which direct PKA to defined intracellular locations (22,23). The majority of these sequester type II PKA subtypes (24)(25)(26), although several dual-function AKAPs can bind either RI or RII (27)(28)(29).…”
mentioning
confidence: 99%